Psychometric evaluation of the Indonesian Version of the Empathy Questionnaire for Children and Adolescents (EmQue-CA) - Wuryaningsih, Emi Wuri; Lusmilasari, Lely; Haryanti, Fitri; Wahyuni, Budi (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Assessing empathy in adolescents is essential for developing effective school bullying prevention programs. However, no validated instrument for evaluating empathy in Indonesian adolescents was previously available. Objective: This study aimed to evaluate the validity and reliability of the Indonesian version of the EmQue-CA and its subscales, providing a tool for assessing empathy in adolescents in Indonesia. Methods: Psychometric testing was conducted in January and February 2024 following the translation and cross-cultural adaptation of the EmQue-CA into Indonesian. A total of 140 junior high school students aged 13 to 15 were selected through multistage sampling. Exploratory Factor Analysis (EFA) was performed to determine the factor structure, while reliability was assessed using Cronbach’s alpha and test-retest reliability. Results: EFA supported a three-factor structure—affective empathy (3 items), cognitive empathy (3 items), and intention to comfort (4 items)—consisting of 10 items in total, which accounted for 65.97% of the variance. The instrument showed strong internal consistency (Cronbach’s alpha = 0.96) and excellent test-retest reliability (r = 0.96, 95% CI: 0.94–0.97). Conclusion: The 10-item Indonesian version of the EmQue-CA is a valid and reliable tool for assessing empathy in adolescents. It can be used by school nurses, healthcare professionals, and educators to support the development of empathy-based interventions in school settings.